Decision-making support among racial and ethnic minorities diagnosed with breast or prostate cancer: A systematic review of the literature. Issue 5 (May 2022) - DeRosa, Antonio P.; Grell, Yendé; Razon, Dominic; Komsany, Alia; Pinheiro, Laura C.; Martinez, Juana; Phillips, Erica
Highlights: Decision aids, trained personnel (e.g., navigators), educational materials are notable decision-making support interventions. Patient-reported outcomes include engagement, satisfaction, decisional regret, health literacy and cultural competence. Decision-making support interventions are associated with positive patient-reported outcomes in racial and ethnic minorities. Abstract: Objective: To describe the types of decision-making support interventions offered to racial and ethnic minority adults diagnosed with breast or prostate cancer and to draw any associations between these interventions and patient-reported quality of life (QoL) outcomes. Methods: We conducted literature searches in five bibliographic databases. Studies were screened through independent review and assessed for quality. Results were analyzed using inductive qualitative methods to determine thematic commonalities and synthesized in narrative form. Results: Searches across five databases yielded 2496 records, which were screened by title/abstract and full-text to identify 10 studies meeting inclusion criteria. The use of decision aids (DAs), trained personnel, delivery models and frameworks, and educational materials were notable decision-making support interventions. Analysis revealed six thematic areas: 1) Personalized reports; 2) Effective communication; 3) Involvement in decision-making; 4) Health literacy; 5) Social support; and 6) Feasibility in clinical setting. Conclusion: Evidence suggests decision-making support interventions are associated with positive outcomes of racial and ethnic minorities with patient-reported factors like improved patient engagement, less decisional regret, higher satisfaction, improved communication, awareness of health literacy and cultural competence. Practice implications: Future decision-making interventions for racial and ethnic minority cancer patients should focus on social determinants of health, social support systems, and clinical outcomes like QoL and survival.